"The hours and times of your desire": Sholto Smith's romantic vision for Colwyn (1925) - Tyler, Linda (Architectural History Aotearoa, 2011)
Early in 1920, French-born architect Sholto Smith (1881-1936) decided to abandon his Moose Jaw practice, and his Canadian wife and family, and emigrate to New Zealand. His decision seems to have been precipitated by a memorable encounter with a woman who would later become a celebrated pianist for the Auckland radio station 1YA, Phyllis Mary Hams (1895-1974). Sholto Smith had met Hams during World War I while he was on leave from the Canadian Expeditionary Force and visiting Colwyn Bay, North Wales. Sholto Smith's major contribution to Arts and Crafts Auckland, the house he designed as a gift for Phyllis Hams on the occasion of their marriage on 3 March 1925, was named Colwyn to memorialise their Welsh meeting place. Despite only living in New Zealand for his last 16 years, Sholto Smith left a legacy of over 100 buildings. Colwyn was a well-placed advertisement for his domestic architecture, and his Arts and Crafts and Tudor house designs were soon in great demand throughout the building boom of the 1920s. Smith had arrived in Auckland on 17 March 1920 and immediately joined the practice of Thomas Coulthard Mullions (1878-1957) and C Fleming McDonald. The latter had been the architect of the original Masonic Hotel in Napier (1897), and the firm originally specialised in hotels and commercial architecture using modern materials including reinforced concrete, but dressing the modernist structure with historicist references. Several of their inner-city Auckland buildings such as the Waitemata and Manukau Council building on the corner of Shortland and Princes Street, Chancery Chambers in O'Connell Street and the Lister building on the corner of Victoria and Lorne Streets, still survive. After McDonald's death, Sholto Smith became a partner in the firm and encouraged Thomas Mullions to move into residential property development in central Auckland: Shortland Flats (1922) was a commercial venture where the architects formed a company owning shares in the building which comprised 24 flats designed to generate rental income. But detached suburban domestic architecture was Sholto Smith's real passion. Before leaving Canada for fresh beginnings in New Zealand, he drew an architectural perspective for his ideal home. He titled this drawing Dreamwold, and his vision for this ideal house was to be realised in Auckland at 187 St Heliers Bay Road. For this house design, Sholto Smith drew inspiration from Canadian colleagues such as British Columbian architect Samuel Maclure (1860-1929) and from the British masters of the Arts and Crafts Movement including CFA Voysey (1857-1951) and MH Baillie Scott (1865-1945). Colwyn is reminiscent of the latter's Corrie Wood (1908) in Letchworth Garden City, Hertfordshire in its adventurous open planning. A little bit of Olde Englande recreated in the South Pacific for his homesick new wife, Colwyn was Sholto Smith's perfect Dreamwold, right down to the text on the wooden mantelpiece over the fireplace. The quote inscribed there is taken from the beginning of Shakespeare's sonnet 57, and seems addressed by Smith to his 30-year-old bride: "Being your slave, what should I do but tend upon the hours and times of your desire?" Epitomising the romantic archetype, Colwyn remains a fine example of the type of Arts and Crafts dwelling that well-to-do Aucklanders aspired to inhabit in the 1920s.